Expectation of DARE/ICAR from Union Budget 2019-20 - Mohapatra, T.; Pal, Suresh; Kumar, Shiv (Indian Farming, 2019)
A budget is a financial plan for allocating money to an organization that uses it to express strategic plans of activities in measurable terms along with the summary of intended expenditures along with proposals for how to meet them with a defined period of a year. The budget is needed to reallocation of resources according to the need of society for the government’s profit maximization to push public welfare. It is through budgetary policies that the government tries to bridge the economic gap in the society besides managing the demand for public enterprises which directly connects with the public interest. Thus, the annual financial statement helps manage the effective and efficient use of economic resources.